Integrated Care for Intracranial Hypertension: Primary Care, Imaging, Pharmacotherapy, and Outcomes Tracking (The Review of Diabetic Studies, 2024)
Background: Intracranial hypertension (IH) is a critical neurological syndrome characterized by elevated intracranial pressure (ICP), which threatens cerebral perfusion and can lead to irreversible injury. Its etiologies range from traumatic brain injury and hemorrhage to idiopathic intracranial hypertension (IIH), making timely diagnosis and management essential.Aim: This study aims to synthesize current evidence on the pathophysiology, diagnostic strategies, and therapeutic interventions for IH, emphasizing integrated care models that combine primary care, imaging, pharmacotherapy, and outcome monitoring.Methods: A comprehensive review of contemporary literature and clinical guidelines was conducted, focusing on ICP physiology, etiological classification, diagnostic modalities—including neuroimaging, lumbar puncture, and invasive monitoring—and tiered treatment strategies. Epidemiological data and outcome metrics were analyzed to contextualize disease burden and therapeutic efficacy.Results: IH manifests through heterogeneous clinical patterns, with headache, visual impairment, and nausea as cardinal symptoms. Neuroimaging remains the cornerstone of diagnosis, supplemented by CSF pressure measurement and ophthalmologic evaluation. Management follows a tiered approach: initial stabilization, hyperosmolar therapy, CSF diversion, and surgical decompression for refractory cases. In IIH, weight reduction and acetazolamide constitute first-line therapy, while venous sinus stenting and optic nerve sheath fenestration are reserved for vision-threatening disease. Prognosis varies by etiology and timeliness of intervention; acute IH carries high mortality without rapid treatment, whereas IIH primarily threatens vision.Conclusion: IH requires an interdisciplinary, etiologically anchored approach to prevent catastrophic neurological and visual sequelae. Early recognition, structured escalation, and continuous monitoring are pivotal for optimizing outcomes.